Habitat characteristics and nest of the ladybird spider, Eresus kollari (Araneae: Eresidae) in South Korea - Jin Hyeok Choi; Daegeun Oh; Na Hyeon Kim; Kil Won Kim (Ecosphere, 2025)
Abstract Eresus kollari is typically found in dry grasslands and stony steppes; however, in South Korea, it has been primarily found in the humid environments of cemeteries. These spiders have highly localized habitats, and their burrowing and nest‐building habits make them difficult to find and observe in the field. This study investigated the cemetery habitat environment, which has not been well‐researched previously. Because direct observation without separating the spiders from their nests is difficult, the relationship between nest size and individual size was studied to estimate the size of the spiders based on their nests. The cemeteries are open and sunny, with loess‐like soil. The ground surface is mainly covered with Korean lawn grass, lacking trees or shrubs, and the herbaceous layer consists of low‐growing plants. The nests of E. kollari consist of an aboveground web canopy and an underground retreat, and they were found just below the grass. The height of the web canopy and the depth of the retreat were not correlated with the individuals' body size. However, the overall nest diameter exhibited a positive exponential relationship with both cephalothorax and abdomen size. In particular, the product of cephalothorax width and length was the most informative parameter for predicting nest diameter. Remains of beetles and ants were found in the web canopy, suggesting that these insects constitute the primary prey of E. kollari. However, in the case of very small ants, it seems that Plagiolepis manczshzurica may be a predator of E. kollari, as ants were found alongside E. kollari remains within the nest. In South Korea, E. kollari is not designated as an endangered species, but its habitat and population have reportedly been in decline. Notably, the habitat observed during the study period was destroyed by construction activities. Therefore, research and conservation measures for this species are necessary.